Fortune hunter : a Miss Fortune mystery - DeLeon, Jana (DeLeon, Jana. Miss Fortune series., 2016)
"Someone has created a fake social media identity and is online romancing the lonely women of Sinful in order to scam them out of money. Because he always seems to pick the perfect targets, Fortune, Ida Belle, and Gertie think he must be either a Sinful resident or someone with a close association to the town. Playing with emotions for pay is dirty pool, but the game turns deadly when one of the women is murdered. Fortune decides the victim must have figured out who the scam artist is and threatened him with exposure. Deputy Carter LeBlanc is hard at work to find the gunman, but sometimes it takes a woman to expose a lady-killer. Fortunately, Swamp Team 3 is on the job."--Back cover.